Delineation of flood risk terrains and rainfall visualisation in the North Western part of Ghana - Dekongmen, B. W.; Kabo-bah, A. T.; Anornu, G. K.; Akpoti, Komlavi; Amo-Boateng, M.; Antwi, E. O.; Boamah, E. O.; Sunkari, E. D. (Springer, 2024)
Flooding, exacerbated by the challenges of climate change, poses a growing threat to communities in the Upper West Region (UWR) of Ghana. This persistent issue, particularly during the rainy seasons has subjected the region to several losses of properties and lives over the years. This has spurred the need for a comprehensive delineation of flood risk terrains (FRTs) and analysis of the rainfall patterns in the region. This study, therefore, started by analysing a digital elevation model (SRTM—DEM) using Jenks Natural Breaks Classification (JNBC) algorithm to delineate potential FRTs map within the region. Further, analysis was performed using Analytical Hierarchy Process Multi-Criteria Decision (AHP-MCD) with the incorporation of six spatial factors (Lineament Density, Elevation, Topographic Wetness Index, Drainage Density, Slope, and Aspect) to generate a comprehensive FRTs map. Climate Hazards Group InfraRed Precipitation with Station data (CHIRPS) from 1992 to 2022 were also visualized in a Jupyter Notebook to assess rainfall patterns in the UWR. Historical flood events data were also analysed to understand the trends of flood events impacts. From the findings, both the JNBC and AHP-MCD algorithms categorized the UWR’s total area into five classes, namely; very high, high, moderate, low, and very low FRTs. The JNBC map had area coverages of 4% (856.278 km2), 7% (1466.685 km2), 12% (2418.642 km2), 35% (7014.96 km2), and 42% (8351.496 km2) from very high risk to very low FRTs, respectively. Notably, the very high risk terrains and high risk terrains were predominantly located along the southeastern and eastern regions, particularly along the Kulpawn River and Sisili River in the UWR. The five classes AHP-MCD map also recorded areas as 0.004% (0.707 km2), 21% (3830.02 km2), 69% (12807.31 km2), 10% (1827.011 km2), and 0.062% (11.535 km2) very high risk to very low FRTs, respectively. These findings further revealed a prevalence of high FRTs along stream and river networks. Interestingly, the validation of the AHP-MCD map over the ground truthing points indicated that the UWR is dominated by moderate FRTs (71.76%), underscoring the region's vulnerability to flooding. The visualization of the spatial rainfall distribution from 1992 to 2022, also highlighted the significance of heavy rainfall years, particularly in 2018, 2019, and 2021, and the month of August as consistent predictors of flood occurrences. A correlation matrix reinforces the strong connection between rainfall and flood-related impacts, such as affected populations, economic costs, and agricultural losses from 2016 to 2021. In light of these findings, UWR residents must prioritize flood-resilient crop cultivation and adhere to flood disaster safety protocols, especially during the critical month of August. These insights hold valuable implications for municipal, district, and community planning policies, offering a foundation for proactive sustainable flood risk mitigation and community resilience efforts in the region.